Department of Animal Genetics and Breeding, Department of Animal Biotechnology College of Veterinary Science, NAU, Navsari, Gujarat, India - Singh, Virender; Chaudhary, Sandhya S; Manat, Tanvi D; Singh, Rana (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present study was conducted to evaluate the effect of dietary supplementation of yeast (Saccharomyces cerevisiae) on haematological parameter in 21 Surti young female buffalo calves (aged 6-12 months). They were divided equally into 3 groups (7 calves in each group) viz. Group I (control), II (supplementation of rumen specific yeast Saccharomyces cerevisiae CNCM I-1077 @ 4x109 cfu/animal/day) and III (supplementation of product of inactivated whole cell yeast Saccharomyces cerevisiae containing elevated levels of L (+) selenomethionine @ selenium inclusion rate in feed at 0.3 ppm). Whole blood was collected at day 0, 45 and 90 and haematological parameters were studied. Except in Group II which showed significant decrease in TEC, all haematological parameters were found within normal physiological range. Thus it was concluded that in female Surti buffalo calves supplementation of yeast and selenized yeast did not cause any significant change in haematological parameters. Kawakami et al., 2010). Amongst several feed Buffalo (Bubalus bubalis) contributes significantly to the dairy sector by producing milk and meat and serving draught purpose. However their performance is hindered by inappropriate feeding, breeding, health and management (Birthal and Jha, 2005). Feeding is of prime importance that affects performance thus signifying the use of feed additives that improves gut health of the animals and results in increased digestion rate as well as better growth performance (Frizzo et al., 2010; 2011 and additives, the dietary supplementation of probiotic yeast Saccharomyces cerevisiae has been reported in several studies to have beneficial effects on production performance of ruminants. It has been reported that yeast culture improved feed intake (Robinson and Erasmus, 2009; Ayad et al., 2013), nutrient digestibility (Wohlt et al., 1991) and feed conversion efficiency as well as growth rate (Lascano et al., 2009) apart from being cost effective (Hutjens, 2007). Yeast supplementation in diet has also been found to
Keywords: yeast; Saccharomyces cerevisiae; haematological parameters; Surti buffalo calves